2020
DOI: 10.1002/mabi.202000299
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced Supramolecular Hydrogels from Attapulgite and Cyclodextrin Pseudopolyrotaxane for Sustained Intra‐Articular Drug Delivery

Abstract: Injectable hydrogels for nonsteroidal anti‐inflammatory drugs’ (NSAIDs) delivery to minimize the side effects of NSAIDs and achieve long‐term sustained release at the targeted site of synovial joint are attractive for osteoarthritis therapy, but how to improve its mechanical strength remains a challenge. In this work, a kind of 1D natural clay mineral material, attapulgite (ATP), is introduced to a classical cyclodextrin pseudopolyrotaxane (PPR) system to form a reinforced supramolecular hydrogel for sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…The morphology of the freeze-dried hybrid hydrogel was investigated by scanning electron microscopy (SEM), and a native hydrogel (without GO, GO 0 PEG 16 CD 60 ) was also observed as comparison. As shown in Figure D,E, the inner morphology of hydrogels was changed from irregular porous aggregates to a sheet-like multilayer structure, which suggested that the introduction of GO sheets can provide a unique 2D constant cross-linkers to construct and stabilize the three-dimensional (3D) networks. , …”
Section: Results and Discussionmentioning
confidence: 98%
“…The morphology of the freeze-dried hybrid hydrogel was investigated by scanning electron microscopy (SEM), and a native hydrogel (without GO, GO 0 PEG 16 CD 60 ) was also observed as comparison. As shown in Figure D,E, the inner morphology of hydrogels was changed from irregular porous aggregates to a sheet-like multilayer structure, which suggested that the introduction of GO sheets can provide a unique 2D constant cross-linkers to construct and stabilize the three-dimensional (3D) networks. , …”
Section: Results and Discussionmentioning
confidence: 98%
“…[54][55][56][57][58] In addition, ATP has a large specific surface area and strong adsorption capacity and can absorb growth factors and nutrients in the surrounding tissues, which is beneficial for promoting the regeneration of defective tissues. 33,[59][60][61] The physical and chemical properties and structural characteristics of ATP make it a potential material for bone tissue repair. 33 Our previous experiments confirmed that nanoattapulgite has good biocompatibility and promotes bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, this hydrogel conjugate has an optimizable release rate regulated by physiological microenvironment. Recently, inartificial clay mineral attapulgite (ATP) was used to produce an enhanced supramolecular hydrogel by cyclodextrin pseudopolyrotaxane (PPR) system (Ha et al., 2021 ). This ATP hybrid hydrogel appears to sustained release of Dcf, good biocompatibility and remarkable anti-inflammatory in vivo test.…”
Section: Targeted Nanomaterials Drug Delivery Systemsmentioning
confidence: 99%